Reading accuracy improvement in Spanish-speaking preschool and primary students: a meta-analysis - Cruz Ripoll Salceda, Juan; Zevallos Polo, Diana Sofía (Revista de Investigación en Logopedia, 2023)
Reading accuracy is a condition for proper understanding of texts. For its improvement, interventions such as phonological awareness training, phonics training, morphology teaching, writing and improvement of motivation have been used. No synthesis studies have been carried out on the improvement of reading accuracy in Spanish speakers, something that this work tries to solve. The search process located 28 independent effects of different interventions on the reading accuracy of students from 1st grade of Preschool Education to 5th grade of Primary Education. Those interventions had a pooled effect of 0.36 after completion and a pooled effect of 0.34 at follow-ups, one or two years after completion. Significantly higher results were found for interventions that included phonological awareness training, initial reading instruction, or comprehension activities. Other interventions showed positive effects, although no significant effect was found in those applied with computer assisted interventions The results are compatible with those obtained in other previous meta-analyses and show different components suitable for initial reading instruction or intervention programs for children with reading accuracy issues.